Inter-caste marriage in bali in the post-reformation era - Sudarma, I Putu (Opción, 2019)
The aim of the study is to investigate Inter-Caste marriage in Bali in the post-reformation era. This research uses a qualitative approach. The type of data used is qualitative data obtained from primary and secondary sources. As a result, there is a change of behavior of Hindu Balinese society in marrying from the pattern of endogamy marriage toward the pattern of eksogami marriage. In conclusion, the inter-caste marriage changes from being closed then tends to be more open. It is caused by several factors such as individual reactions to customs or traditions.